Regulated lentiviral NGF gene transfer controls rescue of medial septal cholinergic neurons - Blesch, Armin; Conner, James; Pfeifer, Alexander; Gasmi, Mehdi; Ramirez, Anthony; Britton, William; Alfa, Ron; Verma, Inder; Tuszynski, Mark H. (Molecular therapy, 2005)
Nerve growth factor (NGF) has been shown to promote survival and function of cholinergic neurons in the basal forebrain in various models of neuronal degeneration in rodents and primates. We examined whether a regulatable in vivo expression system can control the survival of cholinergic neurons after injury, using a tetracycline-regulated promoter ("tet-off" system) to modulate lentiviral NGF gene delivery. Two weeks after lesions to cholinergic neurons, significant cell rescue (65+/-8% neuron survival; P<0.005 compared to controls) was observed when NGF expression was activated. Treatment with the tetracycline analog doxycycline to turn gene expression "off" resulted in a significant loss of cholinergic neurons (only 37+/-5% neurons remained, an amount that did not differ from untreated, lesioned controls). Animals treated with a constitutively active and robust nonregulated NGF expression system showed the same degree of neuronal rescue (73+/-8%) as animals treated with activated tet-regulated vectors. ELISA measurements confirmed that oral treatment of animals with doxycycline reduced NGF protein levels to levels in untreated control subjects. These data demonstrate for the first time that NGF delivery by lentiviral gene transfer using tetracycline-regulated promoters can completely regulate neuronal rescue and protein production in the brain.